Development of AMPIBI: A solar-powered smart waste monitoring and sorting system with cloud integration for environmental preservation and energy conservation - Shafina Moktika Khairani; Kayta Rechia Mazaya; Tengku Naufal Saqib (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Waste management in campus areas remains a significant issue, with trash bins often overflowing due to irregular monitoring and limited awareness among users. This problem is exacerbated by inefficient and energy-consuming traditional waste collection methods, alongside a common failure among students to properly separate waste at the source. The accumulation of unsorted waste not only degrades the campus environment but also represents a missed opportunity for effective recycling and resource recovery. Existing smart bin solutions often focus on a single aspect, such as capacity monitoring or basic sorting, but rarely integrate a comprehensive, energy-independent system tailored for developing-world contexts. To address this multifaceted challenge, a new generation of smart and automated waste management systems is needed. This study introduces a novel solution designed to tackle these issues simultaneously. Methods: This study developed the Automatic Monitoring and Sorting Waste Bin (AMPIBI), an Internet of Things (IoT)-based device designed to automatically sort waste by category and monitor bin capacity in real time. The system integrates cloud-based applications, solar power, and multiple sensors, including moisture, metal, and ultrasonic sensors. The research followed a Research and Development (R&D) approach consisting of problem analysis, design, prototyping, and performance testing. Findings: Experimental results demonstrated that AMPIBI successfully classified waste into three categories: organic, non-metallic inorganic, and metal with an accuracy of 96.67%. The moisture sensor effectively distinguished organic from inorganic waste, the inductive sensor identified metals, and the ultrasonic sensor measured bin capacity. The monitoring system displayed real-time waste status via a cloud platform accessible through mobile devices. Conclusion: AMPIBI improves campus waste management by promoting proper waste disposal, reducing the need for manual intervention, and supporting environmentally friendly practices. Powered by solar energy, the system proved efficient and sustainable, making it a viable solution for cleaner and more energy-conserving campus environments. Novelty/Originality of this article: The novelty of this study lies in the integration of IoT technology, automated waste sorting, and renewable energy into a single system tailored for campus waste management. Unlike conventional bins, AMPIBI provides real-time monitoring, accurate waste classification, and independent solar-powered operation, offering an innovative model for sustainable waste management.